Targeted Brain Delivery Nanoparticles for Malignant Gliomas - Pinto-Paganini, M (Future Medicine Ltd., 2017)
Brain tumors display the highest mortality rates of all childhood cancers, and over the last decade its prevalence has steadily increased in elderly. To date, effective treatments for brain tumors and particularly for malignant gliomas remain a challenge mainly due to the low permeability and high selectivity of the blood-brain barrier (BBB) to conventional anticancer drugs. In recent years, the elucidation of the cellular mechanisms involved in the transport of substances into the brain has boosted the development of therapeutic-targeted nanoparticles (NPs) with the ability to cross the BBB. Here, we present a comprehensive overview of the available therapeutic strategies developed against malignant gliomas based on actively targeted NPs, the challenges of crossing the BBB and blood-brain tumor barrier as well as its mechanisms and a critical assessment of clinical studies that have used targeted NPs for the treatment of malignant gliomas. Finally, we discuss the potential of actively targeted NP-based strategies in clinical settings, its possible side effects and future directions for therapeutic applications. First draft submitted: 4 October 2016; Accepted for publication: 14 October 2016; Published online: 23 November 201. © 2017 Future Medicine Ltd.